0
$\begingroup$

I've been doing a bit of summation work, and I got to$$\sum\limits_{k=1}^{4n+1}\frac 1{n+k}-\sum\limits_{k=1}^n\frac 1{5k-3}-\sum\limits_{k=1}^{n}\frac 1{5k-2}+\frac 35\sum\limits_{k=1}^n\frac 1k\tag1$$And I'm wondering if there is a way to further simplify $(1)$. Specifically, the last three terms, because I feel that you can somehow simplify them even more.

I tried expanding the terms out and got$$\begin{align*} & \sum\limits_{k=1}^n\frac 1{5k-3}+\sum\limits_{k=1}^n\frac 1{5k-2}-\frac 35\sum\limits_{k=1}^n\frac 1k\\ & =\left(\frac 12+\frac 17+\cdots+\frac 1{5n-3}\right)+\left(\frac 13+\frac 18+\cdots+\frac 1{5n-2}\right)-\left(\frac 35+\frac 3{10}+\frac 3{15}+\cdots+\frac 3{5n}\right)\\ & =\left(\frac 12+\frac 13+\frac 17+\frac 18+\cdots+\frac 1{5n-3}+\frac 1{5n-2}\right)-\frac 35\sum\limits_{k=1}^n\frac 1k\end{align*}$$And that's how far I got. Any ideas?

Just as clarification, I started with$$\varphi(5,n)=1+2\sum\limits_{k=1}^n\frac 1{(5k)^3-5k}$$

$\endgroup$
1
$\begingroup$

I do not know how much this could help you.

If you want to use harmonic numbers $$\sum\limits_{k=1}^{4n+1}\frac 1{n+k}=H_{5 n+1}-H_n$$ $$\sum\limits_{k=1}^{n}\frac 1{k}=H_n$$ Now, for the other terms, you can write them using $$\sum\limits_{k=1}^n\frac 1{ak+b}=\frac 1a\sum\limits_{k=1}^n\frac 1{k+\frac ba}=\frac 1a\left( H_{n+\frac ba}-H_{\frac ba}\right)$$

$\endgroup$
  • $\begingroup$ So there isn't really a way to simplify the summation... $\endgroup$ – Crescendo May 31 '17 at 15:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.